2011
DOI: 10.1364/oe.19.007971
|View full text |Cite
|
Sign up to set email alerts
|

Detection of bacteria using bacteriophages as recognition elements immobilized on long-period fiber gratings

Abstract: The paper presents for the first time a study of long-period gratings (LPGs) applied for label-free detection of specific bacteria using physically adsorbed bacteriophages. For the purposes of the experiment a number of highly sensitive LPGs working at the turning point of phase matching curve was fabricated in SMF28 fiber using UV exposure. We show that the device allows for real-time monitoring of phenomena taking place on the sensor's surface, including phage-bacteria interactions. For the applied condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(63 citation statements)
references
References 29 publications
1
62
0
Order By: Relevance
“…Finally, a series of other BREs, based on biointeractions such as enzymatic processes [58,59], biotin/streptavidin affinity [18,33,[60][61][62], virus-specific recognition (bacteriophage T4/Escherichia coli bacteria) [63][64][65][66] and biomimetic affinity processes with molecularly imprinted polymers (MIPs) [67], have been implemented (Table 3). …”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, a series of other BREs, based on biointeractions such as enzymatic processes [58,59], biotin/streptavidin affinity [18,33,[60][61][62], virus-specific recognition (bacteriophage T4/Escherichia coli bacteria) [63][64][65][66] and biomimetic affinity processes with molecularly imprinted polymers (MIPs) [67], have been implemented (Table 3). …”
Section: Applicationsmentioning
confidence: 99%
“…In the challenging field of bacteria detection, E. coli in particular, OFGs have been extensively used combined to bacteriophage T4 [63][64][65][66]: phages are organisms recognizing their host by specific receptor molecules on their surface, with high sensitivity and specificity to the bacteria and good thermal stability [81]. For all these reasons and being nontoxic to humans, as well as cheap and fast to produce, they emerged as a possible alternative to antibodies in biosensor development.…”
Section: Ofg-based Biosensing Based On Other Bresmentioning
confidence: 99%
See 1 more Smart Citation
“…The bacteriophage-based strategy has been successfully adapted for testing of M. tuberculosis (42), with optimization achieved by including recombinant phages containing luciferase genes (43). It was shown that the luciferase assay could be performed at low cost in 2 days (44) and could be applied successfully in laboratories in developing countries (45). Unfortunately, this innovative approach has not been broadly accepted in diagnostic microbiology laboratories, probably due to contamination (46) or phage resistance issues.…”
Section: Technologies For Application In the More-distant Futurementioning
confidence: 99%
“…Wang et al, 2009;Topliss et al, 2010). It should be noted that the number of biosensing applications with LPGs is rapidly growing and it can be foreseen www.intechopen.com that it will represent an area of major interest in coming years (Eggen et al, 2010;Smietana et al, 2011). In this context LPGs realized in Photonic Crystal Fibers are extremely attractive for the possibility to achieve very intense light matter interactions with a unique optofluidic design and with nano-liter sample consumption (Rindorf et al,2006;He et al, 2011).…”
Section: Long Period Gratings: a View Backmentioning
confidence: 99%